Choujin X. Volume 8 - Ishida, Sui (Viz signature., 2025)
"Best friends Tokio and Azuma do everything together, even if most of the time it feels like Tokio is just stumbling along in Azuma's cooler, more talented footsteps. But when they're attacked one night by a superhuman mutant called a choujin, Tokio finally has a chance to shine--by turning into a choujin himself! Operation Old Market, the drug bust Tokio and his friends are attempting to pull off on a tight deadline, is going just as badly as everyone at Yamato Mori expected. In the midst of a high-speed foot chase that could be their big break, Tokio hears a sudden choujin call. He knows he doesn't have time to be distracted, but can he afford to ignore this strange clarion?"--Provided by publisher.